Transcriptome profile analysis reveals the emamectin benzoate-induced genes associated with olfaction and metabolic detoxification in Spodoptera exigua Hübner (Lepidoptera: noctuidae) - Yang Sun; Simin Tao; Wen Zhang; Bin Jiang; Han-Yang Dai; Bao-Sheng Liu; Yong-Jun Zhang; Xiang-dong Kong; Jing Zhao; Li-Xin Bai (All Life, 2022)
Emamectin benzoate (EMB) is one of the high-efficacious pesticide commonly used to control the ferocious economic crop pest S. exigua in the field. The results of S. exigua life table treated with three lethal doses of EMB (LC5, LC20 and LC50) indicated that three lethal doses of EMB could all inhibited the proliferation of S. exigua population effectively by long-lasting inhibit the survival of the S. exigua larvae and per female fecundity significantly (p < 0.05), and the inhibition effects of key life parameters were affected by EMB stress in a dose-dependent manner. 67,123 unigenes with an N50 value of 1941 bp were assembled by RNA-seq data analyses and 44,113 were expressed more than 12 samples. Furthermore, 3517, 3139 and 5135 differentially expressed genes were identified under different lethal doses of EMB treatment. Finally, 16 hub genes and three olfaction-related genes were identified by WGCNA analysis as biomarkers for the EMB response, and the cAMP-dependent proteins, P450 metabolic-related genes and ABC transporter genes might have been involved in response to EMB stress in S. exigua.